A survey on community pharmacists’ interest in providing online pharmacy services - Abu Bakar A,; Ong, Siew Chin; Ooi, Guat See (Pusat Perubatan Universiti Kebangsaan Malaysia, 2023)
There is scarce information on the adoption of e-commerce among retail pharmacists in developing countries. E-pharmacy is defined as community pharmacies provide either singular or a combination of online pharmacy services e.g., virtual dispensing of controlled medicines, online medicinal product consultation, medication-health related online services, health supplements and beauty product online consultation and product delivery services. This study aimed to explore the interest among licensed retail pharmacists to adopt e-commerce as part of their business provisions and to determine key determinants of their interest in providing e-pharmacy services. A self-administered online survey was distributed to 3858 licensed community pharmacists using an email list which was provided by the Pharmacy Enforcement Division, Ministry of Health. The response rate was 9.15% (N=353). Findings showed that 78.2% of the respondents were interested in providing e-pharmacy services. The key determinants of their interest were influenced by community pharmacists’ perceptions towards consumer norms in subscribing to online services, socio-technology trends, pressure from competition and readiness to comply with e-pharmacy regulatory requirements. This study urges the pharmacy authority to formulate business-friendly requirements in empowering community pharmacists to adopt e-pharmacy services and establish a conducive environment for community pharmacists to innovate pharmacy practices. E-pharmacy will benefit the public by providing access to quality medicinal products at competitive prices.